2008
DOI: 10.1071/sr07161
|View full text |Cite
|
Sign up to set email alerts
|

Deriving point and parametric pedotransfer functions of some gypsiferous soils

Abstract: Parametric description of the soil water retention curve as well as the hydraulic conductivity curve is needed for modelling water movement and solute transport in the vadose zone. The objective of this study was to derive pedotransfer functions (PTFs) to predict the water retention curve and the van Genuchten and the van Genuchten–Mualem parameters of some gypsiferous soils. Consequently, 185 gypsiferous soil samples were collected and their physical properties were measured. The particle size distribution wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…In their study, comparison of the derived PTFs with that obtained from Rosetta program (Schaap et al 2001) showed that one should be careful when applying PTFs in pedogenically different areas. The same conclusion was also reported by Homaee and Farrokhian Firouzi (2008) and Cornelis et al (2001). A c c e p t e d M a n u s c r i p t 3 In recent years, development of PTFs for estimating soil hydraulic properties and dielectric properties (Persson et al 2002) has become increasingly popular.…”
Section: Introductionsupporting
confidence: 77%
“…In their study, comparison of the derived PTFs with that obtained from Rosetta program (Schaap et al 2001) showed that one should be careful when applying PTFs in pedogenically different areas. The same conclusion was also reported by Homaee and Farrokhian Firouzi (2008) and Cornelis et al (2001). A c c e p t e d M a n u s c r i p t 3 In recent years, development of PTFs for estimating soil hydraulic properties and dielectric properties (Persson et al 2002) has become increasingly popular.…”
Section: Introductionsupporting
confidence: 77%
“…The fifth point PTF evaluated in this study (Homaee & Firouzi, 2008) (PT5) is a logarithmic function (Equation )): θ=a+b.italicSA+c.italiclog()CL. …”
Section: Methodsmentioning
confidence: 99%
“…Two main groups of PTFs for predicting SWCC have been developed: discrete or point PTFs and continuous PTFs. The point PTFs predict the soil water contents at specific matric potentials (e.g., Adhikary et al, 2008; Al Majou, Bruand, Duval, & Cousin, 2007; Costa et al, 2013; Dashtaki et al, 2010; Fooladmand, 2011; Gupta & Larson, 1979; Homaee & Firouzi, 2008; Hua et al, 2011; Obalum & Obi, 2013; Rawls et al, 1982). Continuous PTFs are functions for predicting the parameters of closed‐form equations between soil water content and matric potential (e.g., Brooks & Corey, 1964; Campbell, 1974; Hutson & Cass, 1987; Saxton & Rawls, 2006; Saxton, Rawls, Romberger, & Papendick, 1986; Van Genuchten, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy with which these properties can be estimated has however a significant effect on the quality of predicted soil hydrological fluxes and states (Montzka et al, 2011). Pedotransfer functions are now popularly used to estimate the soil hydraulic functions from basic soil data such as the particle-size distribu-tion, the bulk density, and the organic C content (Vereecken et al, 1989(Vereecken et al, , 1990(Vereecken et al, , 1992(Vereecken et al, , 2010Schaap et al, 1998Schaap et al, , 2001Jarvis et al, 2002;Rawls and Pachepsky, 2002;Pachepsky et al 2006;Jana et al, 2007;Homaee and Farrokhian Firouzi, 2008;Weynants et al, 2009;Ghorbani Dashtaki et al, 2010). Both point and parametric PTFs have been used for this purpose.…”
Section: A Comparative Study Of Multiple Approaches For Predicting Thmentioning
confidence: 99%